In search of tradition material in Zephaniah 1:7-13 - SD Snyman (Acta Theologica)
The question investigated in this paper is a simple one: are there any indications of the use of tradition material in Zephaniah 1:7-13? Apart from the prominent theme, this paper argues for allusions to at least two of the prominent traditions of salvation present in the Old Testament, i.e. the Sinai tradition and the tradition of the conquest of the land. The mentioning of a coming theophany, a sacrificial meal and a disregard for the first commandment point in the direction of the Sinai tradition. The threat of verse 13 points to the tradition of the land. The positive content of both these traditions are turned against the people. What once was beneficial to them is now a very real threat of doom and disaster.